2017
DOI: 10.1177/1754337117739458
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and field evaluation of a small form factor head impact sensor in un-helmeted play

Abstract: Head impact sensors are increasingly used to quantify the frequency and magnitude of head impacts in sports. A dearth of information exists regarding head impact in un-helmeted sport, despite the substantial number of concussions experienced in these sports. This study evaluated the performance of one small form factor head impact sensor in both laboratory and field environments. In laboratory tests, sensor performance was assessed using a Hybrid III headform and neck. The headform assembly was mounted on a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…The iMG sensors, sampling at 1 kHz (linear acceleration) and 952 Hz (rotational velocity), measured collision metrics comparable with those recorded by an ATD, sampling at 20 kHz, whilst utilising the pendulum-based impactor. Work conducted by Wu et al [64] and Nevins et al [65] have demonstrated the importance of sampling frequency as the duration of the impact decreases. Wu et al [64] investigated the effect of sample rate for wearable inertial sensors by dropping cadaver heads from a single height.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The iMG sensors, sampling at 1 kHz (linear acceleration) and 952 Hz (rotational velocity), measured collision metrics comparable with those recorded by an ATD, sampling at 20 kHz, whilst utilising the pendulum-based impactor. Work conducted by Wu et al [64] and Nevins et al [65] have demonstrated the importance of sampling frequency as the duration of the impact decreases. Wu et al [64] investigated the effect of sample rate for wearable inertial sensors by dropping cadaver heads from a single height.…”
Section: Discussionmentioning
confidence: 99%
“…The authors highlighted that higher bandwidths are required for un-helmeted head impacts, recommending minimum accelerometer and gyroscope bandwidths of 500 Hz in unhelmeted sports conditions [64]. Nevins et al [65] produced ATD head accelerations with magnitudes ranging from 18.4 to 194.0 g, with the higher end achieved through impact velocities of 30 m/s and impact durations of 1-2 ms. They demonstrated that characterising the initial acceleration and rotation peaks, at a frequency of 1 kHz, will result in undersampling of the signal, potentially underestimating the true PLA and PRV values of the ATD headform.…”
Section: Discussionmentioning
confidence: 99%
“…31 A wide variety of head impact sensors is currently available, such as instrumented helmets (e.g., GForceTracker), 5,7,26 headbands (e.g., SIM-G), 18,32,43 mouthguards (e.g., MIG) 16,46 and skin patches (e.g., xPatch). 23,28,33 Increasingly, research studies have used such technology to collect head impact data in sports, commonly American football. 30 Validation of kinematics recorded by head impact sensors in laboratory settings has typically used anthropometric test devices, 44 cadavers 17 and human volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…47 Furthermore, field studies have evaluated the accuracy of sensors to measure head impact exposure using video analysis. 7,16,28,32,33 Such previous research has identified that the absence of observer and/or video confirmation of sensor-recorded events to remove false positives may result in substantial overestimation of head impact exposure. 7,18,32,33 Although filtering algorithms attempt to remove false positives in an automated fashion, some investigations suggest such approaches are limited and not a valid replacement for observer and/or video confirmation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation